In-Situ Infrared Spectra of OH in Pakistan Forsterite at High Temperature - Xiao-Guang Li (MDPI AG, 2021)
The hydroxyl of the gem-grade forsterite from Pakistan was measured by the polarized spectra at room temperature to 1000 °C, showing four unambiguous absorption bands at 3612, 3597, 3579, and 3566 cm−1. Here, we report angle-resolved polarized IR spectroscopy of the crystal-oriented forsterite, which were heated at 1 bar up to 1000 °C in situ to investigate the hydrogen diffusion character. The peak positions of the IR absorbance at 3579 cm−1, 3597 cm−1, and 3566 cm−1 of forsterite decreased linearly depending on the temperature, while the 3612 cm−1 is stable. We discuss that the dipole orientation of the hydroxyl is analyzed by a pleochroic scheme of the integrated absorbance vs. sample to polarizer angle. Our data suggest that the temperature effect cannot be ignored since the absorption coefficients and absorbance band positions of OH may alter.